THE IMPACT OF ONLINE LEARNING PLATFORM ON ENGLISH LANGUANGE PROFICIENCY AMONG HIGH SCHOOL STUDENTS - Hara, Annisa; Darwis, Nirwana; Yauri, Andi Muhammad (Program Pascasarjana, UIN Alauddin Makassar, 2025)
The widespread adoption of digital technology has influenced the way English as a Foreign Language (EFL) is learned, particularly through the use of online learning platforms and artificial intelligence (AI)–based applications. This study examines the role of online learning platforms in supporting English language proficiency among eleventh-grade students at Madrasah Aliyah As'adiyah Uloe. A quantitative descriptive approach was employed, involving 20 students as research participants. Data were collected through a structured questionnaire designed to explore students’ experiences and perceptions of both conventional online platforms, such as Zoom and Google Classroom, and AI-based tools, including ChatGPT and Gemini.This data is taken from analysis using statistical techniques.The findings reveal that AI-based platforms are perceived as helpful in facilitating English learning by providing flexible access to learning, clearer explanations, and assistance in understanding instructional content. Conversely, platforms used for fully online instruction were perceived as less effective than face-to-face learning, as most students indicated a preference for direct classroom interaction. These results suggest that AI-based platforms serve more effectively as supportive learning resources rather than as substitutes for in-person instruction. Therefore, this study recommends the adoption of a blended learning approach that integrates AI-assisted platforms with face-to-face teaching to enhance students’ English language proficiency.